Pengembangan Model Pembelajaran Transformatif Berbasis Etika Pancasila untuk Meningkatkan Keterlibatan - Sunarso; Nasiwan; Suharno; Hidayah, Yayuk; Saputro, Johan Dwi (Journal of Education and Culture, 2024)
This study aimed to develop a transformative learning model based on Pancasila ethics to increase student’s engagement in the learning process. The method of study conducted research and development (R&D) methods by researchers. The detail of discusses were mostly conducted for the development of transformative learning model was done by considering the ethical values of Pancasila in every aspect. This approach aimed to encourage students about they did not only acquire knowledge, but also to increase of understanding for the moral values instilled in Pancasila, such as gotong royong, justice, and unity. In addition, this model emphasized on students' active participation in learning, strengthening their critical and analytical thinking skills. The results showed that the transformative model based on Pancasila ethics had the potential to increase student engagement in the learning process. In Pancasila ethics-based learning, there were social impacts, namely learning motivation, active participation, and problem-solving ability. The implication of this research was that the integration of Pancasila values in learning did not only improve academic achievement, but also shaped student’s character in accordance with the nation's values. Thus, this learning model could be a strong foundation in improving the quality of education and advancing the nation's character development. This research made an important contribution in the context of education development in Indonesia by showing that the integration of Pancasila ethical values in the learning model could be a strong foundation for improving student’s engagement in the learning process and shaping their character in accordance with the nation's values.